Managing community-based conservation in Bobaomby, Madagascar - Élysé Rabearivola Nomenjanahary; Hortensia Rasoanandrasana; Andrew Walsh (Ateliers d'Anthropologie)
Conservation and development projects that prescribe the participation of local stakeholders in decision-making around the sustainable management of their own ecosystems have become commonplace in Madagascar in recent decades, as have scholarly critiques questioning the likelihood that such “community-based conservation” (CBC) efforts can achieve the win-win scenarios they purport to offer Malagasy communities and ecosystems. This article, co-authored by differently positioned collaborators, documents the history of exchanges that have proven fundamental to the development and maintenance of one CBC project in northern Madagascar, focusing especially on the value of ongoing interpersonal relations among community members and external partners.